KAJIAN DESAIN EMBUNG DI TEPIAN KOTA YANG MENGARAH PADA PENGEMBANGAN EKOWISATA BERBASIS EKONOMI KREATIF - Haryati, Sophia Ratna (Jurnal Arsitektur dan Perencanaan (JUARA), 2018)
The form of ecotourism creates environmental sustainability with economic as well as social values for a natural area, is a form of tourism potential management. The purpose of this study was to provide a design recommendation for the local government in making embung arrangement policies that are located on the edge of the city with ecotourism-based localities in the creative economy. The method used is a participatory community research method because the community is the party who knows the problem and needs the most. The main approach of this research is the bottom-up (participatory) model, which involves the community in a series of research processes. A participatory plan focuses on the interests of the community, participatory, dynamic, synergy and legality. The form of research is descriptive with a qualitative approach.